Robotic Assembly and testing Line for dampers and gas springs as a universal solution for Tier 1 manufacturers - Tomasiewicz, Robert (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2025)
ELPLC S.A. since 2004, has developed from a micro-enterprise dealing with the integration of control systems and subcontracting to a significant manufacturer of machines and complex lines for many industries. The dominant activity of the company is the Tier 1 and OEM sector of the automotive industry worldwide, with particular specialization in the production of e-mobility batteries, lights, air conditioning hoses, engine cooling systems, powertrain, dampers and gas springs. The company has its own Research and Development Center (ministerial status of the R&D Center from 2021), experienced engineering team and good production infrastructure. The practical experience and knowledge gathered in cooperation with global customers, especially in the dampers and gas springs industry, have determined that the Company has decided to increase its technological level in this area. This study is an overview of the Company’s most important machines and lines intended for the global Tier 1 market of dampers and gas springs manufacturers. The presented list includes the results of work on the R&D project POIR.01.02.00-00-0056/18-00 – “Development of a product innovation in the form of an innovative technological line for the assembly and testing of dampers and gas springs, for use by international manufacturers of components at the Tier 1 level in the automotive industry”.